The Influence of Work Supervision and Employee Commitment on Work Achievement - Sintia, Sintia; Karneli, Okta (Almana : Jurnal Manajemen dan Bisnis, 2023)
In the development of the business world in Indonesia, companies are required to maintain and improve the quality of work and the quantity of service work. Organizations need people to run them If the company wants to get the desired goals, then one of the things that must be considered is the human being in it namely employees. This research was conducted at PT Multiguna Lestari Abadi Selensen Village. The purpose of this study was to determine the effect of work supervision and employee commitment on work achievement at PT Multiguna Lestari Abadi. Work Supervision and Employee Commitment as independent variables (X) while Work Achievement is the dependent variable (Y). The method used in this research is descriptive and quantitative statistics. The sample for this research was taken from as many as 53 respondents from the total population using the census sampling method. Data obtained from the results of the questionnaire were tested statistically through the SPSS program Statistics 24. The results of the tests conducted show that work supervision has a positive and significant effect on work achievement, employee commitment has a positive and significant effect on work achievement, and work supervision and employee commitment have a significant effect on work achievement.